Construction of Legitimacy in the 2025 Criminal Procedure Code Legislative Speech: A Systemic Functional Linguistic Analysis - Berlian Ayu Pangestu; Endry Boeriswati; Sudarya Permana (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze legitimization strategies in the report delivered by the Chairman of Commission III of the House of Representatives of the Republic of Indonesia (DPR RI) prior to the ratification of the 2025 Criminal Procedure Code (KUHAP). Dewan Perwakilan Rakyat Republik Indonesia The focus of the study is directed toward how language is used to construct legitimacy for legal reform through particular linguistic devices. This research employs Halliday’s Systemic Functional Linguistics (SFL) approach and Theo van Leeuwen’s theory of legitimacy. SFL is used to identify linguistic structures within the speech text, while van Leeuwen’s legitimacy theory is used to explain the legitimizing functions of these linguistic choices. The research data consist of the transcript of the video report delivered by the Chairman of Commission III of the DPR RI during the plenary session on the ratification of the 2025 KUHAP. The analysis was conducted qualitatively by identifying linguistic elements such as modality, nominalization, material processes, relational processes, passive constructions, and evaluative lexical choices. The findings reveal that the speech of Commission III of the DPR RI constructs legitimacy through several major strategies, namely legal-formal authorization, moral evaluation, rationalization, procedural legitimation, and the delegitimization of public criticism. These legitimization strategies are realized through the use of high modality, nominalization, passive constructions, legality-based thematic structures, and evaluative lexical choices that construct the image of the state as a legal, rational, humane, and procedural institution. This study demonstrates that language in legislative speeches functions not only as a means of conveying legal information, but also as an instrument of institutional legitimacy to build public acceptance of state legal reforms. Therefore, this study confirms that language practices in legislative forums play an important role in shaping representations of power, legality, and the relationship between the state and society.